From recreation ecology to a recreation ecosystem: A framework accounting for social-ecological systems. (June 2022) - Miller, Anna B.; Blahna, Dale J.; Morse, Wayde C.; Leung, Yu-Fai; Rowland, Mary M.
Abstract: Recreation ecology has its foundations in the premise that recreationists have a negative impact on ecosystems, and are thus treated as an ecological stressor. However, ecology is the study of interactions between organisms and the environment, not just an organism's impacts on the environment. While we do not dispute the evidence that recreationists can negatively impact ecosystems, recreation can also have positive effects for conservation. Contextualizing interactions between recreation and ecology within broader multi-scale social-ecological systems can advance our scientific knowledge of these interactions to provide a basis for more effective management of protected areas that host recreation. In this paper, we propose the concept that recreation-ecosystem interactions are part of a system with a range of positive, negative, and neutral interactions with feedbacks of variable intensity occurring between multiple levels. We simplify this concept into a two-dimensional quadrant system to describe the spectrum of interactions within a range of social-ecological systems, which could be developed for countless natural and social systems. For example, the social portion of this system includes values such as cultural, health and well-being, tribal, and many others; examples of the ecological portion include vegetation, biodiversity, soils, and more. As an illustrative example, we develop the system for recreation-wildlife interactions. We also emphasize the importance of integrating recreation and wildlife research and management through approaches based on this framework. Future research in this area might be improved by considering this novel framework to balance the needs of humans and protect natural ecosystems in protected area management decisions. Management implications: The framework aims to help outdoor recreation managers and researchers better - Address existing gaps in research and management, - Collaborate with those working in complementary fields, - Develop more integrative recreation planning and management tools, and - Resolve persistent problems in outdoor recreation management.